N2,N2,N4,N4,N6,N6-Hexapropyl-1,3,5-triazine-2,4,6-triamine - Fang-Fang Jian; Yu-Feng Li (Acta Crystallographica Section E, 2008)
The title compound, C21H42N6, was prepared by the reaction of 2,4,6-trichloro-1,3,5-triazine with dipropylamine. The structure of the molecule is tripodal.